Matelogic: Interactive mathematical learning based on challenges - Barrios J.E.M. (2018)
Thanks to CIENCIACTIVA, CONCYTEC, UNSA and the pilot educational institutions San Antonio María Claret and Republica Federal Alemania, for the financing and support in the project called “Plataforma interactiva de programación visual con interfaces tangibles, con aplicación en la enseñanza de matemática en educación básica regular No. 18367-2016”, allowing the improvement of scientific research for the development of the country